O discurso nacionalista dos engenheiros militares - Moreira, Luís Gustavo Guerreiro (2008)
This work examines the speech of nationalist military engineers. I take as a starting point the understanding that the nation, reaching as the default community of modern civilization in the last two centuries, boosted the scientific and technological development, taking the figure of military ahead in these advances. Military Engineering incorporates technical and intellectual elite, historically involved in building a modern and sovereign nation. I focus the Instituto Militar de Engenharia (IME) and the institutions before it, which since the 19th century formed engineers and high level technicians in Brazil. I look at the perception of Brazilian nation revealed in the speeches of commanders and generals of this institution.